Implementation of Interactive Digital Illustrated Story Media to Develop Emotional Intelligence and Global Diversity Dimension Values ​​in 5-6 Year Old Children at Bangun Seranten State Kindergarten: Implementasi Media Cerita Bergambar Digital Interaktif untuk Mengembangkan Kecerdasan Emosional dan Nilai Dimensi Berbhinekaan Global Pada Anak Usia 5-6 Tahun di TK Negeri Bangun Seranten - Yuli Kusuma Astuti; Amrindono (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Emotional intelligence and global diversity values are essential competencies for early childhood in the 21st century. However, conventional teaching methods often fail to engage children in meaningful character education. This study aims to implement interactive digital picture story media to develop emotional intelligence and global diversity dimension values in children aged 5-6 years at TK Negeri Bangun Seranten. This research employs Classroom Action Research (PTK) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 18 children (9 boys and 9 girls) aged 5-6 years in Group B. Data collection techniques included observation, documentation, field notes, and unstructured interviews, analyzed using descriptive qualitative and quantitative methods. The results showed significant improvement in both aspects. In the pre-cycle, only 27.8% of children reached the expected developmental milestones (BSH/BSB) in emotional intelligence, and 22.2% in global diversity values. These figures increased to 61.1% and 55.6% respectively in Cycle I, and reached 88.9% and 83.3% in Cycle II. The interactive digital picture story media, featuring multimedia elements (audio narration, animation, interactive quizzes), successfully enhanced children's emotional awareness, empathy, cultural appreciation, and intercultural communication skills. The study concludes that interactive digital picture story media is an effective pedagogical tool for developing early childhood emotional intelligence and global diversity values.